Body, cosmos and eternity : new research trends in the iconography and symbolism of ancient Egyptian coffins - Sousa, Rogério, (Archaeopress Egyptology ;, 2014)
The studies presented in this volume display an excellent overview on the new trends of research on coffin studies, with diverse contributions concerned either with symbolism or social significance of coffins, museums' collections or archaeological finds. These studies superbly showcase the richness of coffins as documental sources for the study of Egyptian religion, economy and society.